Anti-candidal activity of the Lavandula stoechas L. against pathogenic Candida species isolated from the hospital - Bahar Gedik; Görkem Dülger (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
The purpose of this study is todetermine antimicrobial activity of extracts of L. stoechasL. againstfivedifferent pathogenic Candida species.As test microorganisms, species of Candida (Candida albicans, Candida krusei, Candida tropicalis, Candida guilliermondii and Candida glabrata) which were isolated from the patients appyling to Medical Faculty Hospital of Duzce University were used. Ethyl alcohol, chloroform and ethyl asetate extractions were acquired from the plant via Soxhlet. 25 μl, 50 μl and 75 μl of these extractions were impregnated into sterile discs and the anti-candidal activity spectrums were determined by using the disc diffusion method againts test microorganisms. As the control group standard antifungal antibiotics (Griseofulvin, Fluconazole, Amphotericin b, Miconazole, Nystatin, Flucytosine, Clotrimazole, Ketoconazole, Itraconazole) were used and the outcomes were compared.As a result, it is found out that the extractions acquired from L. stoechas L. plant have a very effective anti-candidal activity as compared with standard antibiotics.On the basis of our results, anti-candidal activity L. stoechas extracts more effective than standard antifungal antibiotics. So, this situation supports the ethnobotany usage of the plant. In addition to this, the potential extracts of the plant commonly used for alternative medicine may be also used for Candidemia treatment in future.